PENINGKATAN KETERAMPILAN MOTORIK KASAR MELALUI PERMAINAN TRADISIONAL KUCING DAN TIKUS: Penelitian Tindakan di Kelompok B TK Cifor Ceria Depok - Puji Yulianty (LPPM Universitas Bina Bangsa, 2023)
The purpose of this research is to improve of gross motor skills of children through the traditional game of cats and mice at TK B Cifor Ceria Kota Depok 2017. The subject of research were 10 children. This research method was based on the research action class of Kemmis and Mc Taggart model included of four steps: (1) planning (2) action (3) observation and evaluation (4) reflection. The study consisted of one cycle, with two times meetings. Data analysis technique were used qualitative and quantitative data. The data were collected used observation instruments, interview non structur and documentation. Results of this research are showed an increased in gross motor skills of children through traditional games, evidenced by the average score of early motor skills crude children 63.61% and cycle I 79.33%. Research findings that the traditional game of cats and mice could increase children gross motor skill in TK B Cifor Ceria